The Constitutional Law in Contemporary Times: Comparison of India and Indonesia - Adnyani, Ni Ketut Sari; Hartono, Made Sugi; Parwati, Ni Putu Ega; Salles, Sergio (Jurnal Suara Hukum, 2024)
Constitutional law in India and Indonesia, although different in governance structure—India as a federal state and Indonesia as a unitary state—faces similar challenges in the era of globalization and technology, such as the protection of minority rights, decentralization, political stability, and adaptation to international standards, while maintaining legal sovereignty and local values. The aim of this research is to analyze the similarities and differences in the fundamental principles of constitutional law between India and Indonesia and their implementation in addressing contemporary challenges such as globalization, democracy, and human rights. This research employs a normative legal method with a legislative approach to analyze and compare the principles of constitutional law in India and Indonesia, through library research involving legal documents, academic literature, and qualitative and comparative analysis techniques to understand the application of law in the context of contemporary challenges. The study finds that although India and Indonesia have different historical and cultural backgrounds, both share fundamental principles of constitutional law such as constitutional supremacy, popular sovereignty, and the protection of human rights, but differ in their governance systems with India adopting parliamentary federalism and Indonesia a presidential unitary system. Both countries face similar challenges in globalization, democracy, and human rights, with India emphasizing the role of judicial review by the Supreme Court and Indonesia strengthening the Constitutional Court. Implementation challenges include issues of pluralism, privacy, decentralization, and responses to digitalization, with each country adjusting its legal framework to address social discrimination and freedom of expression. Keywords: Constitutional Law, Globalization, Decentralization, Indonesia, India.